2009
DOI: 10.1080/09658210903376243
|View full text |Cite
|
Sign up to set email alerts
|

Associations between components of rumination and autobiographical memory specificity as measured by a Minimal Instructions Autobiographical Memory Test

Abstract: Clinical studies have shown that rumination functions as a mediator between overgeneral memory-the tendency to retrieve autobiographical memories in a non-specific format-and depression. Recently, rumination has been dismantled into two distinct subcomponents: reflection, which is more adaptive, and brooding, which is more maladaptive. In the present study we examined the differential relationships of these two rumination subcomponents with autobiographical memory specificity and their mediational role for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
141
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(163 citation statements)
references
References 28 publications
14
141
2
Order By: Relevance
“…The next most common were categoric memories followed by extended memories, with very few semantic associates or omissions. This is similar to the pattern of responses reported by Debeer et al (2009) who used the same minimal instruction version of the AMT with a non-clinical sample.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The next most common were categoric memories followed by extended memories, with very few semantic associates or omissions. This is similar to the pattern of responses reported by Debeer et al (2009) who used the same minimal instruction version of the AMT with a non-clinical sample.…”
Section: Discussionsupporting
confidence: 84%
“…This version is more appropriate for and sensitive to specificity variation in non-clinical samples than the traditional AMT (Debeer, Hermans and Raes 2009;Griffith et al 2009Griffith et al , 2012. Following general instructions to recall and write about memories for personally experienced events, participants were asked to write down a memory in response to each of 12 emotion word cues.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen from the above, studies using non-clinical samples appear to have slightly more non-significant results than studies using clinical samples. It has been suggested that this is due to ceiling effects, since participants are given extensive instructions and examples in the AMT, which may make the task too easy for healthy individuals who might otherwise show a tendency towards reduced specificity (Debeer, Hermans & Raes, 2009 Psychology, 65:2, 137-165, available online at: http://www.tandfonline.com/10.1080Psychology, 65:2, 137-165, available online at: http://www.tandfonline.com/10. /19012276.2013 completing a sentence stem probing overgeneral or specific memories.…”
Section: Maladaptive Rt and Reduced Specificity Of Mttmentioning
confidence: 99%